Six weeks of β-alanine supplementation did not enhance repeated-sprint ability or technical performances in young elite basketball players - Milioni, Fabio (2017)
Supplementation with β-alanine plays an important role as a precursor of carnosine, the most effective intramuscular buffer, and has been seen as a potential ergogenic aid, especially for high-intensity modalities such as basketball. Thus, the aim of the present study was to investigate the effects of 6 weeks of β-alanine supplementation on repeated sprint ability (RSA) and technical performances in young elite Brazilian basketball players. In total, 27 young basketball players (17±1 years) were randomized into a β-alanine group (Gβ - 6.4 g day-1 of β-alanine) and a placebo group (GP - 6.4 g day-1 of dextrose). Before and after the supplementation period the athletes performed a RSA test composed of ten 30 m sprints with two 180° changes of direction interspaced by 30 s of recovery. During the recovery period (i.e., after the sprints) the athletes performed a countermovement jump (CMJ) and a set of three free throws. After 48 h they performed a Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1). Both groups increased the distance covered in the Yo-Yo IR1 after the supplementation period ( p = 0.001). On the other hand, both groups presented impairment in RSA time-performance (total time, best time, and mean time, p ≤ 0.04), while no significant changes were observed for technical task performances (i.e., CMJ and free throws) ( p ≥ 0.07). No between-group interactions were observed for any variable measured ( p ≥ 0.31). Thus, 6 weeks of β-alanine supplementation did not improve RSA or technical performances in young elite basketball players.